Cinesonica : sounding film and video - Birtwistle, Andy (Manchester University Press, 2014)
This book takes an interdisciplinary approach to the growing area of research and teaching of film sound. It explores new ways of approaching film sound by addressing the limited theoretical horizon of established critical perspectives on film sound.